2005
DOI: 10.1074/jbc.m507187200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Delta Induces Apoptosis of Vascular Smooth Muscle Cells through Induction of the Tumor Suppressor p53 by Both p38-dependent and p38-independent Mechanisms

Abstract: Apoptotic death of vascular smooth muscle cells (SMCs) is a prominent feature of blood vessel remodeling. In the present study, we examined the novel PKC isoform protein kinase C delta (PKC␦) and its role in vascular SMC apoptosis. In A10 SMCs, overexpression of PKC␦ was sufficient to induce apoptosis, whereas inhibition of PKC␦ diminished H 2 O 2 -induced apoptosis. Moreover, evidence is provided that the tumor suppressor p53 is an essential mediator of PKC␦-induced apoptosis in SMCs. Activation of PKC␦ led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 59 publications
6
50
1
1
Order By: Relevance
“…We hypothesized that PKCδ would phosphorylate p53, leading to p53 activation and consequent renal apoptosis. This hypothesis was mainly based on 2 considerations: (a) a role for p53 has been demonstrated in cisplatin nephrotoxicity (34,(40)(41)(42)(43)(44)(45)(46)(47), and (b) PKCδ has recently been implicated in p53 phosphorylation and activation (56,57). This hypothesis, seemingly logical, is nonetheless not supported by our results.…”
Section: Mapks and Not P53 As Downstream Mediators Of Pkcδ Signalincontrasting
confidence: 56%
“…We hypothesized that PKCδ would phosphorylate p53, leading to p53 activation and consequent renal apoptosis. This hypothesis was mainly based on 2 considerations: (a) a role for p53 has been demonstrated in cisplatin nephrotoxicity (34,(40)(41)(42)(43)(44)(45)(46)(47), and (b) PKCδ has recently been implicated in p53 phosphorylation and activation (56,57). This hypothesis, seemingly logical, is nonetheless not supported by our results.…”
Section: Mapks and Not P53 As Downstream Mediators Of Pkcδ Signalincontrasting
confidence: 56%
“…We propose the following chain of events underlies the SFHFKSGSL peptide-mediated membrane blebbing. In response to prolonged treatment with PMA or oxidative stress caused by ionizing radiation, activated PKC␦ can be cleaved, presumably by caspase-3, and the released catalytic domain is translocated to the nucleus (21,63), although there is a lag of several hours between treatment and PKC␦ cleavage. Nuclear PKC␦ phosphorylates and thereby inactivates both the DNA damage checkpoint protein hRad9 and DNA-dependent protein kinase; the latter is essential for double strand break repair (64,65).…”
Section: Discussionmentioning
confidence: 99%
“…The greatest numbers of spectra for phosphorylated peptides were identified for two serine positions in BVR, Ser 21 and Ser 230 . To demonstrate PKC␦ specificity, GST-BVR, without any prior kinase treatment, was also mapped in parallel, using chymotrypsin and trypsin digestion.…”
Section: Characterization Of An Hbvr-based Peptide As a Pkc␦mentioning
confidence: 99%
See 1 more Smart Citation
“…4,12 Numerous studies have shown that PKCd is involved in proapoptic signaling upon phorbol ester stimulation and after DNA damage. 13 Therefore, we tested PMAinduced cell death in the patient's cells (EBV-transformed B cells and PBMCs).…”
Section: Pma-induced Apoptosis Is Defective In Pkcd Deficiencymentioning
confidence: 99%